Study on the effect and mechanism of Ershiyiwei Lvronghao concentrated Pills in the treatment of nonalcoholic fatty liver disease - Wu, Yexin; Chen, Bin; Long, Jintao; Pai, Mingxin; Xiao, Zhiyong; Huang, Qun; Li, Kang; Ye, Bengui (Frontiers in Pharmacology, 2026)
BackgroundErshiyiwei Lvronghao Concentrated Pills (ESYWLRHW) is the concentrated pill developed and prepared based on the classical prescription in Xizang: Ershiwuwei Lvronghao Pills (ESWWLRHW). However, its effect on nonalcoholic fatty liver disease (NAFLD) remains unclear. The aim of this study is to clarify the therapeutic effect and mechanism of ESYWLRHW on NAFLD.MethodsHigh-Performance Liquid Chromatography-Quadrupole Time of Flight-Mass Spectrometry/Mass Spectrometry (HPLC-Q-TOF-MS/MS) was used to analyze the components of ESYWLRHW. The NAFLD model was established by feeding Sprague-Dawley (SD) rats with high-fat diet (HFD) for ten consecutive weeks, and different doses of ESYWLRHW and positive drugs were given for intervention treatment in the last 6 weeks. The pathological and molecular changes of rats in each group were determined after the whole experimental procedure with pathological sections and ELISA experiments, and the metabolomics, proteomics and transcriptomics were used to investigate the possible mechanism.ResultsIn this study, 206 compounds of ESYWLRHW were identified. In vivo experiments, ESYWLRHW administration significantly ameliorated the pathological manifestations in NAFLD model rats, including attenuating the abnormal body weight gain, reducing the accumulation of hepatic and peripheral fat, and improving dyslipidemia, liver function, and systemic inflammatory response. Metabolomic analysis further revealed that ESYWLRHW treatment upregulated the levels of specific metabolites, such as 12-keto-leukotriene B4 (12-keto-LTB4), 20-COOH-LTB4, glycocholate (GCA), and dehydroepiandrosterone sulfate (DHEAS). Integrated multi-omics analysis and subsequent verification indicated that the therapeutic effects of ESYWLRHW might be mediated by modulating the expression of Peroxisome Proliferator-Activated Receptors (PPARs), which in turn regulated downstream signaling pathways including nuclear factor erythroid 2-related factor 2 (Nrf2) and the Nuclear Factor-kappa B (NF-κB)/NOD-like receptor family, pyrin domain-containing 3 (NLRP3)/Caspase-1 axis.ConclusionIn summary, ESYWLRHW can regulate the three metabolic pathways: arachidonic acid metabolism, primary bile acid biosynthesis and steroid hormone biosynthesis, and improve oxidative stress and inflammation in NAFLD rats by regulating the expression of PPARs protein, and ultimately alleviate NAFLD.